Dietary nitrate supplementation enhances exercise performance in peripheral arterial disease - Kenjale, Aarti A.; Ham, Katherine L.; Stabler, Thomas; Robbins, Jennifer L.; Johnson, Johanna L.; VanBruggen, Mitch; Privette, Grayson; Yim, Eunji; Kraus, William E.; Allen, Jason D. (Journal of applied physiology (1985), 2011)
Peripheral arterial disease (PAD) results in a failure to adequately supply blood and oxygen (O 2 ) to working tissues and presents as claudication pain during walking. Nitric oxide (NO) bioavailability is essential for vascular health and function. Plasma nitrite (NO 2 − ) is a marker of vascular NO production but may also be a protected circulating “source” that can be converted to NO during hypoxic conditions, possibly aiding perfusion. We hypothesized that dietary supplementation of inorganic nitrate in the form of beetroot (BR) juice would increase plasma NO 2 − concentration, increase exercise tolerance, and decrease gastrocnemius fractional O 2 extraction, compared with placebo (PL). This was a randomized, open-label, crossover study. At each visit, subjects ( n = 8) underwent resting blood draws, followed by consumption of 500 ml BR or PL and subsequent blood draws prior to, during, and following a maximal cardiopulmonary exercise (CPX) test. Gastrocnemius oxygenation during the CPX was measured by near-infrared spectroscopy. There were no changes from rest for [NO 2 − ] (152 ± 72 nM) following PL. BR increased plasma [NO 2 − ] after 3 h (943 ± 826 nM; P ≤ 0.01). Subjects walked 18% longer before the onset of claudication pain (183 ± 84 s vs. 215 ± 99 s; P ≤ 0.01) and had a 17% longer peak walking time (467 ± 223 s vs. 533 ± 233 s; P ≤ 0.05) following BR vs. PL. Gastrocnemius tissue fractional O 2 extraction was lower during exercise following BR (7.3 ± 6.2 vs. 10.4 ± 6.1 arbitrary units; P ≤ 0.01). Diastolic blood pressure was lower in the BR group at rest and during CPX testing ( P ≤ 0.05). These findings support the hypothesis that NO 2 − -related NO signaling increases peripheral tissue oxygenation in areas of hypoxia and increases exercise tolerance in PAD.